Molecular Beacons - Yang, Chaoyong James; Tan, Weihong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Molecular Beacons explains working principle of molecular beacons, discusses their design, synthesis, purification and characterization, explores their thermodynamic and kinetic properties, and more importantly, reviews their in vivo and in vitro applications with the emphasis on the design and modification of molecular beacons for in vivo mRNA imaging applications. This book is designed to bring together in a single resource an organized and comprehensive view of molecular beacons and will be a valuable resource for academic, clinical and industrial scientists and graduate students who may consider exploring molecular beacons in their research or practice. Chaoyong James Yang is the Lu Jiaxi Professor of Chemistry at Xiamen University, China. Weihong Tan is a Distinguished Professor of Chemistry and Biomedical Engineering at Hunan University, China and also a University of Florida Distinguished Professor and V. T. and Louis Jackson Professor of Chemistry at the University of Florida, USA.
Design, Synthesis, Purification and Characterization of Molecular Beacons -- Thermodynamic and Kinetic Properties of Molecular Beacons -- Application of Molecular Beacons in Real-Time PCR -- Molecular Beacons for Detection of Single Nucleotide Polymorphisms -- Molecular Beacons on Solid Surfaces -- Functional materials for signal amplification of molecular beacons -- Engineering Molecular Beacons for Advanced Applications -- Excimer Molecular Beacon -- Strategies for Delivering Molecular Beacons into Cells -- Molecular Beacons for Intracellular Analysis: Challenges and Successes -- Molecular Aptamer Beacons.
Keywords: Chemistry; Gene expression; Analytical biochemistry; Biotechnology; Nucleic acids; Cytology; Chemistry; Biotechnology; Gene Expression; Nucleic Acid Chemistry; Cell Biology; Analytical Chemistry